Why Didn’t You Text Me? Poststudy Trends From the DepoText Trial - Muñoz Buchanan, Cara R. (Clin Pediatr (Phila), 2017)
OBJECTIVE: To evaluate the longitudinal impact of a 9-month text message intervention on participant adherence beyond the intervention to highly effective contraceptive methods among urban adolescent and young adult women enrolled in the DepoText randomized control trial (RCT). STUDY DESIGN: Retrospective longitudinal cohort study of long-term follow-up data from the DepoText RCT. Sixty-seven female participants (aged 13–21 years) using depot medroxyprogesterone acetate (DMPA) were recruited from an urban academic adolescent practice in Baltimore, Maryland. The principal outcome measured was a comparison of contraceptive method choice between the control and intervention groups during the 20 months postintervention. RESULTS: Intervention participants were 3.65 times more likely to continue using DMPA or a more efficacious method at the 20-month postintervention evaluation (odds ratio 3.65, 95% CI 1.26–10.08; P = .015). CONCLUSION: Participation in the DepoText trial was associated with continued use of DMPA or a more effective contraceptive method almost 20 months after the intervention exposure ended.